Gauss-Codazzi formalism to brane-world within Brans-Dicke theory - Abdalla, M. C. B. [UNESP]; Guimaraes, M. E. X.; da Silva, J. M. Hoff [UNESP] (Springer, 2008)
We apply the Gauss-Codazzi formalism to brane-worlds within the framework of Brans-Dicke gravity. The compactification is taken from six to five dimensions in order to formalize brane-world models with hybrid compactification in scalar tensor theories.